Determinantes estruturais de saúde e sua relação com a cobertura universal de saúde e métricas de cárie não tratada em escala global - Amaral Júnior, Orlando Luiz do (2023)
Although structural determinants play a central role in explaining the health-disease process of populations, their relationship with universal health coverage and oral health conditions in populations remains understudied. Given the context described, it becomes imperative to undertake investigations to understand the underlying connections and thus comprehensively underpin global public health improvement efforts. Therefore, this thesis comprises two studies. The first aimed to examine structural factors, including governance, macroeconomic policies, public policies, social policies, and cultural aspects correlated with the Global Universal Health Coverage (UHC) Index in the periods of 2010 and 2019. The second study describes the distribution of years lived with disability (YLDs) as well as the prevalence and incidence of untreated dental caries in both deciduous and permanent dentition in the years 2010 and 2019, considering structural determinants. Both methodological approaches are ecological studies. Data from the Global Burden of Disease Study (GBD) 2021 cycle, encompassing 204 countries and territories, were used for the analyses. Both studies underscore the need for adopting comprehensive public policies in the journey toward a future of global health equity. As we project our vision for the coming years, it is of utmost importance for decision-makers, leaders, and international organizations to collaborate in realizing the goal of universal health coverage and addressing disparities in oral disease burden. Building equitable and sustainable healthcare systems requires a broad approach that encompasses structural determinants.